(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To review the clinical features of abortion and intrauterine fetal demise with histopathological findings in their placenta Methods: A retrospective study conducted at Kathmandu University Dhulikhel Hospital from 2008 to 2018. Results: A total of 431 placentas were examined over one decade. One third of them (33.2%) had abortion. Mean age of the patients with abortion was 24.72±5.5 years and that of intrauterine fetal demise (IUFD) was 25.36±5.4 years (p=0.2288). Two thirds of patients with abortion presented with vaginal bleeding and/or lower abdominal pain; 73% of IUFD presented with decreased fetal movement. Gross anomaly was the most common comorbid condition in abortion group while pre/post term, antepartum hemorrhage and PIH were the commoner conditions in IUFD group. In this study, 17.4% abortion cases and 18.3% IUFD cases were with histopathologically proven infection. Conclusions: Placental examination helps in revealing unseen pathologies in cases of poor obstetric outcomes in the form of abortion or fetal demise. The service provider should collect and provide required clinical information before studying the placenta to establish a hidden diagnosis.